Territorial Manifestations in Times of Globalization: Implications for State-Centrism in International Relations - Aleksandrova, Boryana (International Studies. Interdisciplinary Political and Cultural Journal, 2019)
Globalization challenges the state-centric realist view of space and authority within International Relations. Using multifaceted concepts of territoriality and non-territoriality, this article goes into three versions of current territorial fragmentation or connectivity – deterritorialization, extraterritorialization and reterritorialization. They are to enable us to reveal the proliferation of globally relevant social and power dynamics above, below and within the state domain. At the same time, they are to illuminate the ambivalent role of states played in an era of global interconnectedness.